Streptococcus suis in employees and the environment of swine slaughterhouses in São Paulo, Brazil: Occurrence, risk factors, serotype distribution, and antimicrobial susceptibility - Soares, Taíssa Cook Siqueira [UNESP]; Gottschalk, Marcelo; Lacouture, Sonia; Megid, Jane [UNESP]; Ribolla, Paulo Eduardo Martins [UNESP]; Pantoja, José Carlos Defigueiredo [UNESP]; Paes, Antonio Carlos [UNESP] (My University, 2015)
Streptococcus suis is an important pathogen in the swine industry. This article is the first to report the occurrence, risk factors, serotype distribution, and antimicrobial susceptibility of S. suis recovered from employees and environmental samples of swine slaughterhouses in Brazil. Tonsillar swabs from all 139 pig-slaughtering employees and 261 environmental swabs were collected for detection of S. suis and serotyping by monoplex and multiplex polymerase chain reaction, respectively. Antimicrobial susceptibility was determined by the disk-diffusion method. Although S. suis was not detected in any of the tested employees, it was isolated from 25% of the environmental samples. Significant differences (P < 0.05) in the occurrence of S. suis were observed between slaughterhouses and between areas of low, medium, and high risk. The most frequent serotypes were 4 and 29, each accounting for 12% of the isolates, followed by 5, 12, 21, and 31, each accounting for 6%. High rates of susceptibility to the antimicrobials doxycycline (100%), ceftiofur (94%), ampicillin (81%), and cephalexin (75%) were observed. However, multidrug resistance was observed in all the isolates. Because S. suis is present in the environment of swine slaughterhouses, on carcasses and knives, as well as on the hands of employees in all areas, all employees are at risk of infection.